Analysis of efficiency between self-check in and conventional check in with queue method (case study at terminal 3 Soekarno-Hatta airport) - Tukhas Shilul Imaroh; Abdul Hafaz Ngah; Sugiyono Sugiyono (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Queues occur as a consequence of the limited-service facilities. Queuing systems can occur in various places and times, one of which is checking in aircraft at Soekarno-Hatta International Airport Cengkareng. Comparative analysis of the time efficiency of the queuing system needs to be done to help make decisions on the implementation of the check in system to improve service performance in order to achieve customer satisfaction. This study aims to analyze the comparison of queue time efficiency between self-check in and conventional check using the queuing method. The population in this study are prospective passengers who will check-in at Terminal 3 Soekarno - Hatta Airport, the sample used is passengers who come and queue at the ticket check-in counter of Soekarno - Hatta Airport Tangerang to take boarding passes from February 2022. Sampling method using purposive sampling. The data collection method used primary data and secondary data. The data analysis method uses the Queuing System Performance analysis with the Multiple Line Queuing Model (M/M/S). The results of the research are expected to help solve problems, assist decision making and determine policies related to long queues at check-in activities at airports.